1995
DOI: 10.1111/j.1540-6261.1995.tb05166.x
|View full text |Cite
|
Sign up to set email alerts
|

The New Issues Puzzle

Abstract: Companies issuing stock during 1970 to 1990, whether an initial public offer ng or a seasoned equity offering, have been poor long-run investments for investors. During the five years after the issue, investors have received average returns of only 5 percent per year for companies going public and only 7 percent per year for companies conducting a seasoned equity offer. Book-to-market effects account for only a modest portion of the low returns. An investor would have had to invest 44 percent more money in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

70
773
4
18

Year Published

1999
1999
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 2,507 publications
(865 citation statements)
references
References 50 publications
(54 reference statements)
70
773
4
18
Order By: Relevance
“…We focus in particular on the "abnormal return" (AR) method where accumulated returns to event firms are compared to accumulated returns of Index, typically matched on the basis of firm size, age, sector, and offer size. The findings of this study are in line with the results of many previous studies conducted the long run underperformance of IPOs, like (Ritter, 1991;Levis, 1993;Loughran & Ritter, 1995;Drobetz et al, 2005). These studies summarized and highlighted important empirical regularities; that the long run abnormal returns are often quite negative.…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…We focus in particular on the "abnormal return" (AR) method where accumulated returns to event firms are compared to accumulated returns of Index, typically matched on the basis of firm size, age, sector, and offer size. The findings of this study are in line with the results of many previous studies conducted the long run underperformance of IPOs, like (Ritter, 1991;Levis, 1993;Loughran & Ritter, 1995;Drobetz et al, 2005). These studies summarized and highlighted important empirical regularities; that the long run abnormal returns are often quite negative.…”
Section: Resultssupporting
confidence: 81%
“…Levis also confirms Ritter (1991) findings of statistically significant long run IPOs underperformance. Loughran and Ritter (1995) examined a sample of 4,753 US IPOs issued during ), Loughran and Ritter report that whether initial public offerings (IPOs) or seasoned equity offerings (SEOs) are significantly underperformed relative to non-issuing firms for five years after the offering date, the average annual return during the five years after issuing is only 5%for firms conducting IPOs, and only 7% for firms conducting SEOs. Barber and Lyon (1997) analyzed 1,798 US IPOs issued during July 1963 to December 1994 using CAR and BHAR, Fama and French three -factors model.…”
Section: Previous Literaturementioning
confidence: 99%
“…In addition, the use of limited risk factors to estimate abnormal return leads the factor model approaches tend to be misspecified (Kothari and Warner (1997), Daniel andTitman (1997), andJegadeesh (2000). Loughran and Ritter (1995) suggested that the multi-factor model shows a lower ability in detecting abnormal returns. Fama and French (1992) recommended that future research needs to involve more factors and variables of firm characteristics to build the more representative estimation model of return.…”
Section: Introductionmentioning
confidence: 99%
“…Apart from the selection of the appropriate method to measure abnormal returns (BHAR-method), the selection of suitable benchmarks is highly important as results change quite sensitively to the choice of respective benchmarks (Loughran & Ritter, 1995). In order to provide a very detailed analysis, exonerated from biases, various benchmarks are applied, with the aim of giving a comprehensive foundation of the right argumentation of the results.…”
Section: Selection Of Suitable Benchmarksmentioning
confidence: 99%